Force-time course parameters and force fatigue model during an intermittent fatigue protocol in motorcycle race riders - Marina, M.; Rios, M.; Torrado, P.; Busquets, A.; Angulo-Barroso, R. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Fatigue in forearm muscles may be critical for motorcycle riders in relation to performance and forearm disorders. Force-time course parameters were examined to better characterize the reduction in the maximal force generating capacity (MVC) during an intermittent fatigue protocol (IFP) specifically designed for motorcycle riders. Also, a mathematical force fatigue model is proposed. Forty motorcyclists (aged 27.6 ± 6.8 years) performed an IFP that simulated the braking gesture and posture of a rider. Fatigue was confirmed by a 40% decrement of the normalized MVC in comparison with basal value. Contraction time increased in comparison with basal condition (P = 0.034). Relaxation kinetics presented two phases: (a) a pre-fatigue phase where half relaxation time (HRTraw) and normalized (HRTnor) decreased (P = 0.013) while relaxation rate (RRraw) remained unchanged; and (b) a fatiguing phase where HRTraw, HRTnor increased and RRraw decreased (P = 0.047). Normalized RRraw (RRnor) declined progressively (P = 0.016). The proposed nonlinear force fatigue model confirmed a satisfactory adjustment (R2 = 0.977 ± 0.018). This mathematical expression derived three patterns of force fatigue: three-phase, exponential and linear, representing 70%, 13%, and 17% of the participants, respectively. Overall, these results provided further support to force fatigue theoretical and applied proposals.